A Tale of Community College Transfer Pathway: US-ELs' Trajectories toward Healthcare Programs. Issue 9 (2nd September 2022) - Li, Kuang
ABSTRACT: U.S.-educated English learners (US-ELs) who aspire to obtain a bachelor's degree are often guided by their high school counselors to attend community colleges first, and are assured that they can always transfer to a university later. However, the literature on US-ELs' community college transfer is virtually nonexistent. This 13-month multiple-case study documented the transfer trajectories of four US-ELs who intended to enroll in healthcare programs at a community college first and then transfer to a university. Findings showed that all four students fell short of their original transfer aspirations. Five major factors were identified to account for the differences between students' original plans and actual trajectories, including 1) inadequate high school preparation in science, 2) late enrollment and poor performance in their first program-related courses, 3) linguistic insecurity, 4) underdeveloped knowledge of their intended programs and transfer process, and 5) underuse of advising services. The findings indicate that the community college transfer pathway does not guarantee transfer for US-ELs.